Evaluation of cultivars of the genus Cynodon with or without nitrogen - Cecato, Ulysses (2008)
Chemical composition, in vitro digestibility of dry matter (IVDDM), organic matter (IVDOM) and cell wall (IVDCW), green dry matter production (GDMP), plant re-growth (PR) and stem/leaf ratio (S/L) of five cultivars of the genus Cynodon at two levels of N fertilization (0 and 400 kg/ha) in the summer and spring are provided. CP did not differ (P > 0.05) from other grasses in chemical composition. However differences (P ≤ 0.05) occurred due to nitrogen level and cut intervals. Values for ADF and NDF were affected (P ≤ 0,05) by grass, nitrogen level and cut intervals. Grasses showed statistical differences (P ≤ 0.05) for IVDDM, IVDOM and IVDCW. Tifton 44 showed the highest digestibility for all parameters, while Estrela Porto Rico the lowest digestibility for IVDCW. Other grasses did not differ from each other. There were no differences (P > 0.05) among the fertilized cultivars for GDMP. Under no fertilization GDMP of Tifton 85 cultivar was higher than that of Tifton 44 and coast cross cultivars. Under N application PR of Tifton 85 was higher than that of Estrela Porto Rico and purple star grasses. S/L ratio of the Tifton 85 cultivar was different (P < 0.05) from Estrela Porto Rico e purple star grasses ratios. Application of N increased GDMP, PR and S/L of the cultivars.